Determinantes genéticos da hanseníase em uma população do Rio Grande do Norte - Araújo, Sérgio Ricardo Fernandes de (2008)
Background: Leprosy can cause severe disability and disfigurement and is still a major health in different parts of the world. Only a subset of those individuals exposed to the pathogen will go on to develop clinical disease and there is a broad clinical spectrum amongst leprosy patients. The outcome of infection is in part due to host genes that influence control of the initial infection and the host´s immune response to that infection. Aim: Evaluate if polymorphisms type SNP in the 17q118q21 chromosomic region contribute to development of leprosy in Rio Grande do Norte population. Material and methods: A sample composed of 215 leprosy patients and 229 controls drawn from the same population were genotyped by using a Snapshot assay for eight genes (NOS2A, CCL18, CRLF3, CCL23, TNFAIP1, STAT5B, CCR7 and CSF3) located in chromosomic region 17q118q21. The genotype and allele frequency were measured and statistical analysis was performed by chi-square in SPSS version 15 and graph prism pad version 4 software. Results: Ours results indicated that the markers NOS2A8277, NOS2A8rs16949, CCR78rs11574663 and CSF38rs2227322 presented strong association with leprosy and their risk genotype were GG, TT, AA and GG respectively. The risk genotypes for all markers associated to leprosy presented recessive inheritance standard. When we compared the interaction among the markers in different combination we find that the marker NOS2A8277 associated with CCR78rs11574663 presented highest risk probability to development of leprosy. When we evaluated the haplotype of the risk markers it was found a haplotype associated with increase of the protection (CSF38rs22273228CC, CCR78 rs115746638GA, NOS2A8rs169498CT and NOS2A82778GA). The association of the clinical forms paucibacilary and multibacilary with markers showed that to the markers NOS2A8 2778GG, CCR78rs115746638AA and CSF38rs22273228GG there were a strong influence to migration to multibacilary pole and to marker NOS2A8rs169498TT the high proportion was found to the paucibacilary form. Conclusions: Changes in the genes NOS2A, CCR7 and CSF3 can influence the immune response against Mycobacterium leprae. The combination among these polymorphisms alters the risk probability to develop leprosy. The markers type SNP associated to development of the leprosy also are linked to clinical forms and its severity being the polymorphism NOS2A8rs169498TT associated with paucibacilar form and the polymorphisms NOS2A82778GG, CCR78rs115746638AA and CSF38rs22273228GG associated to multibacilar form